Impact of gymnastics training on the health-related physical fitness of young female and male artistic gymnasts - Kolimechkov, S.; Kiuchukov, I.; Janev, I.; Petrov, L.; Alexandrova, A.; Zaykova, D.; Stoimenov, E. (Science of Gymnastics Journal, 2019)
Artistic gymnastics can be practised from an early age and develops the main components of physical fitness. The aim of this study was to assess the physical fitness of young competitive artistic gymnasts from Bulgaria. A total of 161 gymnasts (81 females and 80 males), who were divided into three groups (from 5-8, 9-11, and 12-15 years of age), with sports experience from 12 to 180 months, took part in this study. All of the participants completed the extended version of the Alpha-Fit physical fitness test battery, with European norms being applied to calculate percentile scores for each fitness test. The height-for-age percentile scores in the groups between the ages of 9-11 and 12-15 were significantly lower from the 50th percentile of the international norms, both for male and female gymnasts. Gymnasts showed substantially lower body fat, and only one gymnast was assessed as overweight, with two being classified as obese. The percentile scores of the standing long jump and the 4x10 m SRT in the groups were significantly greater than the 50th percentile of the available European norms. The percentile scores of the VO2max in all female groups were also higher than the 50th percentile of the European norms, while those for males did not differ from the 50th percentile, except in the 5-8 age range. Artistic gymnastics improves the physical fitness components and positively influences children`s physical development. Both female and male artistic gymnasts had better physical fitness in most parameters, in comparison with their peers.